Metal–Ligand Multiple Bonding in Thorium Phosphorus and Thorium Arsenic Complexes. Issue 66 (7th November 2017) - Vilanova, Sean P.; Alayoglu, Pinar; Heidarian, Mohammad; Huang, Patrick; Walensky, Justin R.
Abstract: The complexes (C5 Me5 )2 Th(EHTipp)2, (E=P or As; Tipp=2, 4, 6‐triisopropylphenyl), provide a ligand framework that results in facile access to rare Th–E multiple bonds. The reaction of (C5 Me5 )2 Th(EHTipp)2 with KN(SiMe3 )2, proceeds cleanly to the desired bridging phosphinidiide or arsinidiide complex, [(C5 Me5 )2 Th(μ2 ‐ETipp)(μ2 ‐EHTipp)K]2 under ambient conditions. In the absence of a chelating agent, the potassium cation of one monomeric unit interacts with the aryl ring of a second monomer to form a bridged dimer. In the presence of 2, 2, 2‐cryptand, the terminal phosphinidene complex, [(C5 Me5 )2 Th=PTipp(PHTipp)][K(2, 2, 2‐cryptand)] is isolated. Using X‐ray crystallographic analysis, we have determined these complexes display the shortest Th−P and Th−As bond lengths reported. Abstract : Thorium gets some Pi : Bridging phosphinidiide and arsinidiide complexes have been synthesized from the deprotonation of one phosphorus or arsenic in (C5 Me5 )2 Th[EH(2, 4, 6‐ i Pr3 C6 H2 )]2 ; E=P, As. Using 2, 2, 2‐cryptand to sequester the cation leads to just the second terminal thorium phosphinidene complex and the shortest thorium–phosphorus bond to date at 2.6024(9) Å. All three complexes have significant thorium–ligand multiple bonding.